Antioxidant therapy to prevent preeclampsia - A Randomized controlled trial - Spinnato, Joseph A.; Freire, Salvio; Pinto e Silva, Joao Luiz; Rudge, Marilza Vieira Cunha [UNESP]; Martins-Costa, Sergio; Koch, Matthew A.; Goco, Norman; Santos, Cleide de Barros; Cecatti, Jose Guilherme; Costa, Roberto; Ramos, Jose Geraldo; Moss, Nancy; et al. (Lippincott Williams & Wilkins, 2007)
OBJECTIVE: To study whether antioxidant supplementation will reduce the incidence of preeclampsia among patients at increased risk.METHODS: A randomized, placebo-controlled, double-blind clinical trial was conducted at four Brazilian sites. Women between 12 0/7 weeks and 19 6/7 weeks of gestation and diagnosed to have chronic hypertension or a prior history of preeclampsia were randomly assigned to daily treatment with both vitamin C (1,000 mg) and vitamin E (400 International Units) or placebo. Analyses were adjusted for clinical site and risk group (prior preeclampsia, chronic hypertension, or both). A sample size of 734 would provide 80% power to detect a 40% reduction in the risk of preeclampsia, assuming a placebo group rate of 21% and alpha=.05. The a level for the final analysis, adjusted for interim looks, was 0.0458.RESULTS: Outcome data for 707 of 739 randomly assigned patients revealed no significant reduction in the rate of preeclampsia (study drug, 13.8% [49 of 355] compared with placebo, 15.6% [55 of 352], adjusted risk ratio 0.87 [95.42% confidence interval 0.61-1.25]). There were no differences in mean gestational age at delivery or rates of perinatal mortality, abruptio placentae, pre-term delivery, and small for gestational age or low birth weight infants. Among patients without chronic hypertension, there was a slightly higher rate of severe preeclampsia in the study group (study drug, 6.5% [11 of 170] compared with placebo, 2.4% [4 of 168], exact P=.11, odds ratio 2.78, 95% confidence interval 0.79-12.62).CONCLUSION: This trial failed to demonstrate a benefit of antioxidant supplementation in reducing the rate of preeclampsia among'patients with chronic hypertension and/or prior preeclampsia.